Tindak Pidana Pengguguran Kandungan oleh Korban Perkosaan dalam Pembaharuan Hukum Pidana Indonesia - Kadek Jiyoti Mahayana; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2021)
Abortion treatment is a problem that is contrary to any religion and the laws of Indonesia. However, it is known that there are also those who support and those who oppose abortion, which often happens to women who experience pregnancies as a result of rape, because women victims of rape who undergo abortion also need attention to their psychological conditions who are traumatized about the events that have happened to them. This study aims to examine the legal protection of rape victims who have aborted based on the Criminal Code and explain the criminal act of abusing the womb by victims of rape in the reform of the Criminal Code. This type of research is normative legal research with a conceptual approach. Primary and secondary legal data sources. The results of the study show that the legal protection of rape victims who have aborted their womb in the Criminal Code has been neglected by clearly prohibiting all abortion activities either at the request of the woman herself or with the help of others as described in Article 346 to Article 349 of the Criminal Code but there are exceptions where women rape victims who do abortions which can cause psychological trauma, the regulation of which is stipulated in law no. 36 of 2009 Article 75 paragraph (2). In the Criminal Law Reform Regulations on abortion are regulated in the Draft Criminal Code 2019, Chapter XXI, which is included in the second part of the crime against life regarding abortion, article 470 to article 472 of the 2019 RUUKUHP.